Podcast-based Teaching Media through the Role-Playing Model to Improve Elementary School Students’ Speaking Skills - Ni Kadek Ananda Kumara Shinta; I Made Tegeh; I Nyoman Laba (Universitas Pendidikan Ganesha, 2024)
This study was motivated by the low speaking skills of students in elementary school, as well as the unoptimal utilization of learning media in learning activities. This development research aims to develop podcast-based teaching media on the speaking skills of grade V students. This development study uses the ADDIE model, which is composed of five stages, namely: (1) analysis, (2) design, (3) development, (4) implementation, and (5) evaluation. This study takes the subject of podcast-based teaching media, while the object of development research is the validity of media content, material content, user response, and media effectiveness. Data collection methods are interviews, observations, and questionnaires. The instruments used to collect data are observation guidelines, rating scale sheets, interview guidelines, sheets and questionnaires. The results showed that, the podcast-based teaching media that has been produced obtained a validity index with high content validity qualifications, the material on the content of the podcast-based teaching media that has been produced obtained a validity index with high content validity qualifications. The level of achievement of student responses to podcast-based teaching media gain very good qualifications. Podcast-based teaching media is effective in improving the speaking skills of grade V elementary school students.